Detection of Branched Cracks in Beam-like Structures - TUFIȘI, Cristian (Presa Universitară Clujeană, 2024)
The book aims to bring contributions in the field of science and engineering practice, mainly in structural health monitoring by presenting methods of identifying the position and severity of cracks in structures by using natural frequencies and determining the accuracy of these methods in detecting different types of damages.